Mind the gap: From Inter- to Transculturality in Dutch Literature? - Lücke, Nicole M.H. (Werkwinkel, 2016)
This paper focuses on current issues relating to cultural encounters in contemporary Dutch literature. The starting point is transculturality - a concept suggesting a new way of looking at culture that is frequently applied as an alternative to concepts such as multi- and interculturality. This article deals with theoretical issues as well as with the question whether transculturality is appropriate when characterizing how cultural contacts are represented in literature. The results of this case study based on a literary analysis of Kader Abdolah’s short story “Een onbekende trekvogel” provide a strong argument for modifying the concept of transculturality and sharpening awareness for increasing interrelations of individuals, societies, institutions and nations.